Penerapan Model Pembelajaran Contextual Teaching And Learning (CTL) Pada Mata Pelajaran Al-Quran Hadis - Abdul Basir; Bintan Maulida Safitri; Sunarto Sunarto (Jurnal Ilmu Pendidikan Islam, 2023)
This study aims to determine the effect of applying the Contextual Teaching and Learning (CTL) learning model on student learning outcomes in Al-Quran Hadith class XI MA Al Asyhar Sungonlegowo Bungah Gresik subject. This research is quantitative. The data collection uses questionnaires and documentation. The issue of this research is class XI students. The population is 44 students. The researcher used a random sampling technique, namely random classes, by taking classes XI IPA and XI IPS, where the entire sample was 34 students. The data analysis technique researchers use is a simple linear regression analysis technique using IBM SPSS Statistics 25. The results of the research conducted show that the application of the Contextual Teaching and Learning (CTL) learning model in the Al-Quran Hadith subject at MA Al Asyhar Sungonlegowo with the mean calculation of the results of distributing questionnaires is equal to 61.91%. There is a significant increase in student learning outcomes after the implementation of the Contextual Teaching and Learning (CTL) learning model has a substantial effect on the learning outcomes of Al-Quran Hadith, as evidenced by an increase in the mean value of 77.71 to 88.56, obtained from the t-test and F-test respectively namely 2.231 and 4.978 with a significance of 0.033 < 0.05. The effect of applying the Contextual Teaching and Learning (CTL) learning model on the learning outcomes of Al-Quran Hadith MA Al Asyhar Sungonlegowo students has an R-value of 0.367